ATP Antagonizes Thrombin-Induced Signal Transduction through 12(S)-HETE and cAMP - Burzaco, Jaione (2013)
In this study we have investigated the role of extracellular ATP on thrombin induced-platelet aggregation (TIPA) in washed human platelets. ATP inhibited TIPA in a dose-dependent manner and this inhibition was abolished by apyrase but not by adenosine deaminase (ADA) and it was reversed by extracellular magnesium. Antagonists of P2Y1 and P2Y12 receptors had no effect on this inhibition suggesting that a P2X receptor controlled ATP-mediated TIPA inhibition. ATP also blocked inositol phosphates (IP1, IP2, IP3) generation and [Ca2+]i mobilization induced by thrombin. Thrombin reduced cAMP levels which were restored in the presence of ATP. SQ-22536, an adenylate cyclase (AC) inhibitor, partially reduced the inhibition exerted by ATP on TIPA. 12-lipoxygenase (12-LO) inhibitors, nordihidroguaretic acid (NDGA) and 15(S)-hydroxy-5,8,11,13- eicosatetraenoic acid (15(S)-HETE), strongly prevented ATP-mediated TIPA inhibition. Additionally, ATP inhibited the increase of 12(S)-hydroxy-5,8,10,14-eicosatetraenoic acid (12(S)-HETE) induced by thrombin. Pretreatment with both SQ- 22536 and NDGA almost completely abolished ATP-mediated TIPA inhibition. Our results describe for the first time that ATP implicates both AC and 12-LO pathways in the inhibition of human platelets aggregation in response to agonists.